Correlatos valorativos das atitudes frente à aposentadoria - Melo, Rômulo Lustosa Pimenteira de (2014)
This dissertation aimed to verify if Human Values could explain attitudes towards retirement through the reasons for retiring. Were adopted the techniques of Classical Test Theory (CTT) and Item Response Theory (IRT) to adapt and validate two measures of Attitudes towards retirement. One of them is semantic differential (Osgood method) and the other is method of equal appearing intervals (Thurstone method). Were also used a questionnaire about Reasons to retire, the Basic Values Questionnaire and a demographic questionnaire. To meet the proposed objectives, two studies were conducted. The first involved a sample of 200 people over 50 years of age [mean = 57.37 years (SD = 7.51)], 63% are female, 61.3% are married or have a partner, average years of schooling of 14.01 years (SD = 9.71) and 65.80% retired. The results showed a unifactor structure for the two scales of attitudes. The semantic differential [(22 items) (α = 0.97)] had a mean item discrimination of 2.50 (SD = 0.85) and average psychometric information of 8.41 (SD = 3.81).The scale of apparently equal intervals [(30 items) (α = 0.87 )] had a item discrimination mean of 1.36 (SD = 0.56) and a psychometric information mean of 1.36 (SD = 0 ,11). With regard to the correlateds, there was a positive correlation of the subfunctions Interactive and Normative with the attitudes toward retirement, as well as positive correlation between More free time and Attitudes. The explanation of the interactive values on attitudes was mediated by More free time. The second study, besides trying to replicate the correlates found, tested reduced versions of Attitudes measures. The sample comprises of 230 participants, over 50 years [mean = 57.56 years (SD = 5.48)], 62.3% female, 65.1% married living with a partner, with an average years of schooling of 15.52 years (SD = 9.75) and 56.80 % retired. A Confirmatory Factor Analysis admitted a one-dimensional structure for the semantic differential Attitude Scale [6 items (χ2 / df = 2.14 , GFI = 0.97, AGFI = 0.94, CFI = 0.98 and RMSEA = 0.068)]. No significant differences were observed between the scores of discrimination of the two scale versions [p = 0.49, CI 99 % (LI - 0.48) (LS - 0.50)] .The same was not observed for the equal appearing intervals Attitude Scale (10 items) intervals, because the measure did not show evidence of sampling adequacy for factor analysis (KMO = 0.58), had low levels of fit (χ2 / df = 2 , 37, GFI = 0.86 , AGFI = 0.81, CFI = 0.60 and RMSEA = 0.078) and inadequate levels of scalability (Hs) ranged from 0.02 to 0.11 . According to the correlates, the semantic differential attitude measure showed, again, a significant positive correlation with the subfunction Existence (r = 0.15, p ≤ 0.05) and Interactive (r = 0.15, p ≤ 0.05), but in this study, no significant correlation was observed between the variable More free time and the subfunctions Achievement, Suprapersonal and Normative. Finally, we trust that these results can subsidize retirement preparation programs that uses the Human Values to enhance positive attitudes toward retirement.